2005
DOI: 10.1111/j.1742-4658.2004.04504.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of IMPDH2, survivin, topoisomerase I and vimentin increases sensitivity to methotrexate in HT29 human colon cancer cells

Abstract: We determined differentially expressed genes in HT29 human colon cancer cells, both after short treatment with methotrexate (MTX) and after the resistance to MTX had been established. Screening was performed using Atlas Human Cancer 1.2K cDNA arrays. The analysis was carried out using Atlas image 2.01 and genespring 6.1 software. Among the differentially expressed genes we chose for further validation were inosine monophosphate dehydrogenase type II (IMPDH2), inosine monophosphate cyclohydrolase and survivin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…IMPDH2 appears to have a greater role in patient response to mycophenolate therapy because it is five times more sensitive than IMPDH1 to inhibition by MPA. In addition to its role in immunosuppression therapy, studies have shown that IMPDH2 mRNA levels are elevated in tumor cells (Natsumeda and Carr, 1993) and are significantly associated with resistance to cancer chemotherapy (Penuelas et al, 2005;Hong et al, 2006;Fellenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…IMPDH2 appears to have a greater role in patient response to mycophenolate therapy because it is five times more sensitive than IMPDH1 to inhibition by MPA. In addition to its role in immunosuppression therapy, studies have shown that IMPDH2 mRNA levels are elevated in tumor cells (Natsumeda and Carr, 1993) and are significantly associated with resistance to cancer chemotherapy (Penuelas et al, 2005;Hong et al, 2006;Fellenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an association between vimentin and tumour development, progression, and chemosensitivity was suggested by various gene profiling studies (Zajchowski et al, 2001;Mellick et al, 2002;Penuelas et al, 2005). Vimentin was selectively overexpressed in highly aggressive breast cancer cells (Zajchowski et al, 2001).…”
mentioning
confidence: 99%
“…One study reported that the DHFR amplified, MTX-resistant human adenocarcinoma cell line, HT29, is highly sensitive to BR and MTX combination treatment, but not sensitive to either BR or MTX alone. 21 It was suggested that concomitant inhibition of DHFR and IMPDH may account for the increased sensitivity observed. However our data suggests that downregulation of DHFR by BR may also contribute to drug synergism.…”
mentioning
confidence: 99%